Rancangan Strategi Bisnis PT.Pel Berlian Pulau Mandangin Tahun 2021 – 2023 : Indonesia - Rohman, Abdur Rohman; Hidayati, Aprihatiningrum (Journal of Emerging Business Management and Entrepreneurship Studies, 2021)
This thesis discusses about the business strategy design 2021 - 2023 period. The formulation of business strategy is carried out by conducting an external analysis, in order to obtain opportunities and threats that can affect the shipping industry, then formulate the strengths and weaknesses of PT. BPM, then performs the formulation of alternative strategies using internal and external analysis (IE) and the TOWS Matrix. And in order to obtain several alternative strategic options. The last step is choosing a strategy using the Quantitative Strategic Planning Matrix (QSPM).  QSPM analysis shows that the selected strategy for the 2021 - 2023 period is a product development and planning business implementation of the chosen strategy.